Thin-layer chromatography of mycobactins and mycolic acids for the identification of clinical mycobacteria - Leite, CQF; Barreto, AMW; Leite, SRA (Soc Brasileira Microbiologia, 1995)
Forty seven strains of mycobacteria (35 strains isolated from clinical specimens and 12 reference strains) were analyzed for mycobactin and mycolate production by thin-layer chromatography (TLC). Different growth conditions had little or no effect on the production of individual mycobactins and the reproducibility of mycobactin Rf values. Mycolate profiles of isolated strains were compared with those of reference strains. Clinical isolates belonging to the same species showed the same profiles. The combined evaluation of mycobacterial products by TLC allowed the identification of pathogenic and opportunist cultivable mycobacteria. on routine examination, the analysis of mycobactin and mycolate production constitutes an adequate procedure for the characterization and identification of myobacteria.
Keywords: mycobacteria; identification; mycobactin; mycolic acid; thin layer; chromatography